Market Concentration in Construction Tenders in West Papua - Bagas Johantri; Rachma Aprilia; Sopian Sopian (Yayasan Ilomata, 2023)
This study aims to determine the level of market concentration in construction work tenders in West Papua and to investigate the correlation between the market concentration index and the average participation in tenders, the number of work packages, and average tender savings. West Papua has privileges in procurement and has special autonomy funds for development. The study uses tender data from 2018-2022 and employs the Herfindahl-Hirschman Index (HHI) and Concentration Ratio 4 (CR4) to calculate market concentration. The results indicate that, based on HHI, the market concentration in the building construction and civil engineering subsectors is generally low, except for civil engineering in 2022. However, based on CR4, the market concentration in the building construction subsector is moderate, and in the civil engineering subsector, it is low, except for 2018. Moreover, there is a negative correlation between the number of packages and average participants, as well as between the number of packages and CR4 values. The findings of this study can be useful for construction providers to understand the competition in tenders and assist the government in developing competitive procurement strategies. Future research can investigate the economic benefits of local West Papua businesses when market concentration is low.